1996
DOI: 10.1002/(sici)1096-9071(199607)49:3<223::aid-jmv11>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

A non-radioactive PCR enzyme-immunoassay enables a rapid identification of HPV 16 and 18 in cervical scrapes after GP5+/6+ PCR

Abstract: In previous studies, general primer mediated PCR (GP5+/6+ PCR) was applied successfully to detect a broad spectrum of human papillomaviruses (HPV) in cervical scrapes. In order to facilitate PCR based HPV detection and typing, a colourimetric microtitre plate based hybridisation assay was developed. The method utilised one biotinylated primer (bio-GP6+) in the GP-PCR. Biotinylated PCR products were captured on streptavidin coated microtitre plates, denaturated and hybridised to digoxigenin (DIG) labelled HPV s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 27 publications
1
43
0
Order By: Relevance
“…DNA quality was checked by β-globin, house keeping gene, amplification using Polymerase Chain Reaction (PCR) under the following; initial denaturation at 94 o C for 5 min, 40 cycles with the cycling of 94 o C for 1 min, 60 o C for 1 min, 72 o C for 1 min and then final extension at 72 o C for 5 min. The primer sequences were as follows (Jacob et al, 1996): β-globin sense ACA CAA CTG TGT TCA CTA GC and β-globin antisense GAA ACC CAA GAG TCT TCT CT. The amplified products were subjected to electrophoresis and visualized by UV transilluminator.…”
Section: Dna Extractionmentioning
confidence: 99%
“…DNA quality was checked by β-globin, house keeping gene, amplification using Polymerase Chain Reaction (PCR) under the following; initial denaturation at 94 o C for 5 min, 40 cycles with the cycling of 94 o C for 1 min, 60 o C for 1 min, 72 o C for 1 min and then final extension at 72 o C for 5 min. The primer sequences were as follows (Jacob et al, 1996): β-globin sense ACA CAA CTG TGT TCA CTA GC and β-globin antisense GAA ACC CAA GAG TCT TCT CT. The amplified products were subjected to electrophoresis and visualized by UV transilluminator.…”
Section: Dna Extractionmentioning
confidence: 99%
“…16 A previous study demonstrated that, within the range of 1 Â 10 to 1 Â 10 6 genome equivalents, the EIA OD value obtained after 1 hr of substrate incubation shows a linear relation with the amount of input DNA. 17 Consequently, EIA ODs can semiquantitatively assess the relative viral load.…”
Section: Hpv Dna and Viral Load Analysismentioning
confidence: 99%
“…After deparaffinization with xylene, twice rehydration in absolute ethanol and discharge the remaining ethanol, all of samples were dried at room temperature to ensure that no residual ethanol (Ngamkham et al, 2013). Genomic DNA extraction was performed using QIAamp DNA Mini kit (QIAGEN, Germany) according to the manufacturer's instruction and genomic DNA quality was evaluated by polymerase-chain reaction with β-globin primers (Jacob et al, 1996); sense 5'-ACA CAA CTG TGT TCA CTA GC-3' and antisense 5'-GAA ACC CAA GAG TCT TCT CT-3'. Total volume of 25 μl PCR mixture was consisted of 5 μl extracted DNA, 0.4μM of sense and antisense primers, 2.5U Taq polymerase, 200nM of each dNTPs and 1.5mM MgCl 2 .…”
Section: Sample Preparation and Dna Extractionmentioning
confidence: 99%